Ecotoxicity of benzo[a]pyrene assessed by soil microbial indicators. (9th July 2014) - Cheng, Jinjin; Song, Jing; Ding, Changfeng; Li, Xiaogang; Wang, Xingxiang
Abstract The ecotoxicity of benzo[a]pyrene (BaP) to soil microorganisms was evaluated using the following microbial indicators: soil microbial biomass, respiration, nitrification, and Shannon index. Two soil types, udic ferrosols and aquic cambisols, were amended with 0 mg/kg, 1 mg/kg, 10 mg/kg, 100 mg/kg, 500 mg/kg, or 1000 mg/kg BaP; incubated at 25 °C; and tested on days 28, 60, and 180. The Shannon index was extremely insensitive to BaP. Microbial biomass and respiration could not be classified as sensitive indicators because of their relatively high 10% effect concentration (EC10) values. Nitrification was the most sensitive indicator in both soils and could be the preferred microbial indicator for testing the ecotoxicity of BaP. Higher toxicity of BaP was exhibited in udic ferrosols than in aquic cambisols, and the ecotoxicity of BaP decreased with incubation time. Extending the 28‐d incubation time, which is suggested in the International Organization for Standardization and Organisation for Economic Co‐operation and Development guidelines, to 60 d was recommended for future microbial toxicity tests of BaP. On day 28, the EC10 values for microbial biomass, respiration, and nitrification were 71 mg/kg, 43 mg/kg, and 3.4 mg/kg in aquic cambisols and 51 mg/kg, 22 mg/kg, and 1.3 mg/kg in udic ferrosols, respectively. On day 60, these values were 106 mg/kg, 59 mg/kg, and 19 mg/kg in aquic cambisols and 77 mg/kg, 40 mg/kg, and 6.9 mg/kg in udic ferrosols. These values could be used in combination to derive ecotoxicological soil screening levels of BaP. Environ Toxicol Chem 2014; 33:1930–1936. © 2014 SETAC